The influence of nutrition maturity and canopy density on the incidence of apple bitter rot - Everett, K.R.; Timudo-Torrevilla, O.E.; Scheper, R.W.A.; Shaw, P.W.; Wood, P.N.; Mundy, D.C.; Wallis, D.R. (New Zealand Plant Protection, 2016)
Royal Gala apple fruit were inoculated with Colletotrichum acutatum (the cause of apple bitter rot) conidia at monthly intervals throughout the season in three growing regions in New Zealand The resultant lesion size was measured on harvested fruit after 9 weeks of coolstorage to generate a disease curve Nutrient composition Brix and mean weight of uninoculated fruit were measured at monthly intervals The canopy density of the trees at harvest was also determined These results were compared with the area under the disease curve (AUDC lesionsize days) Starch pattern index and fruit weight at harvest were positively correlated with AUDC suggesting that fruit towards the end of the season was more susceptible to infection by C acutatum Nitrogen was also positively correlated with AUDC Canopy density potassium and boron were negatively correlated although the relationship with potassium needs confirmation There was no relationship of apple bitter rot with calcium